2022
DOI: 10.3390/antiox11081620
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide Increases Nitric Oxide Levels and Decreases Oxidative Stress in an In Vitro Model of Preeclampsia

Abstract: (1) Background: The bioavailability of nitric oxide (NO) and oxidative stress are important events related to the pathophysiology of preeclampsia (PE). In this present study, we aimed to evaluate the antioxidant effect of glibenclamide (GB) on the NO synthesis, oxidative stress, and antioxidant capacity in endothelial cells incubated with plasma from preeclamptic (PE) and normotensive pregnant women (NT). (2) Methods: Human umbilical vein endothelial cells (HUVECs) were incubated with a plasma pool from 10 NT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Thus, both extracts significantly reduce MDA levels while significantly increasing GSH, CAT, and SOD levels, similar to glibenclamide, as compared to the diabetic group of rats. Glibenclamide has been found to possess antioxidant effects [ 37 , 38 ]. The ability of our extracts to reduce the imbalance between ROS generation and enzymatic antioxidant activity in diabetic rats may explain the improvement in oxidative stress indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both extracts significantly reduce MDA levels while significantly increasing GSH, CAT, and SOD levels, similar to glibenclamide, as compared to the diabetic group of rats. Glibenclamide has been found to possess antioxidant effects [ 37 , 38 ]. The ability of our extracts to reduce the imbalance between ROS generation and enzymatic antioxidant activity in diabetic rats may explain the improvement in oxidative stress indicators.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of PE, a variety of endothelial cell dysfunctions can be observed, such as decreased proliferation, migration, and angiogenesis ability, cellular inflammatory response, oxidative stress, and vasoconstriction dysfunction . Researchers have found that relieving endothelial cell dysfunction through various means can treat PE, such as Priscila Rezeck Nunes using glyburide to enhance the antioxidant capacity of endothelial cell . Liu et al uses procyanidin B2 to attenuate sFlt-1-induced endothelial dysfunction and impaired angiogenesis, Gu et al uses esomeprazole to inhibit hypoxia/endothelial dysfunction-induced autophagy in PE .…”
Section: Discussionmentioning
confidence: 99%
“…20 Researchers have found that relieving endothelial cell dysfunction through various means can treat PE, such as Priscila Rezeck Nunes using glyburide to enhance the antioxidant capacity of endothelial cell. 21 Liu et al uses procyanidin B2 to attenuate sFlt-1-induced endothelial dysfunction and impaired angiogenesis, 22 Gu et al uses esomeprazole to inhibit hypoxia/endothelial dysfunctioninduced autophagy in PE. 23 Previous researchers have confirmed that endothelial cells are an effective target for the treatment of PE.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The fasting blood glucose levels were assessed before induction and 72 days post alloxan induction using the Easy-Touch-GCU device (Bioptik Technology, Inc., Jhonghua, Taiwan). Only the rats showing fasting blood glucose levels exceeding 126 mg/dL were categorized as diabetic [55,56] and were included in the next phase of the study.…”
Section: In Vivo Anti-diabetes Analysis In An Alloxan-induced Diabeti...mentioning
confidence: 99%